Occipital neuralgia following thoracic herpes zoster: case report - Demir, Caner Feyzi; Akalin, Yahya; Berilgen, Said (Kare Publ, 2011)
Paroxysmal shooting or stabbing pain in the dermatomes of the nervus occipitalis major or nervus occipitalis minor is defined as occipital neuralgia. The initial cause of the neuralgia appears to be from inflammation, damage or irritation of these nerves. In this article, we present a patient with occipital neuralgia followed by thoracic herpes lesion.
Keywords: Occipital neuralgia; zoster sine herpete